2012
DOI: 10.13064/ksss.2012.4.2.003
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Word Frequency and Neighborhood Density on Spoken Word Segmentation in Korean

Abstract: The purpose of this study was to investigate whether a segmentation unit for a Korean noun is a 'syllable' and whether the process of segmenting spoken words occurs at the lexical level. A syllable monitoring task was administered which required participants to detect an auditorily presented target from visually presented words. In Experiment 1, syllable neighborhood density of high frequency words which can be segmented into both CV-CVC and CVC-VC were controlled. The syllable effect and the neighborhood dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
(8 reference statements)
1
2
0
2
Order By: Relevance
“…Furthermore, Yi and Pak (1997) reported that significant differences were emerged by word frequency and phonological change rules. Song et al (2012) also, confirmed an interaction between word frequency and syllable neighbourhood size at lexical processing. It demonstrated that the word segmentation could be influenced by both prelexical and lexical processing.…”
Section: Introductionsupporting
confidence: 61%
“…Furthermore, Yi and Pak (1997) reported that significant differences were emerged by word frequency and phonological change rules. Song et al (2012) also, confirmed an interaction between word frequency and syllable neighbourhood size at lexical processing. It demonstrated that the word segmentation could be influenced by both prelexical and lexical processing.…”
Section: Introductionsupporting
confidence: 61%
“…This fact is discussed in more detail in Section 3. To our knowledge, the only published study of ND effects involving spoken Korean, Song, Nam, & Koo, (2012), investigated the effects of word frequency and ND on spoken word segmentation. This study used a syllable-based ND measure, as was done in other studies of spoken word segmentation (e.g., Cutler, Mehler, Norris, &Segui, 1986 andMehler, Dommergues, Frauenfelder, &Segui, 1981), but it renders it nevertheless incompatible with the majority of ND studies on English, which used a phoneme-based measure.…”
Section: Previous Research On Neighborhood Density In Koreanmentioning
confidence: 99%
“…Word frequency effect refers to the observation that the more frequent the occurrence of a word, the easier it is to recognize that word. To prove the word frequency effect, Song, Nam, and Koo (2012) reported that when an experimenter heard a speech composed of high-frequency and low-frequency words mixed with noise, the experimenter recognized high-frequency words better than low-frequency words.…”
Section: A Game-based Learning Judgment Systemmentioning
confidence: 99%